2004
DOI: 10.1063/1.1818337
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation pressure: A “phase contrast” agent for x-ray phase contrast imaging

Abstract: We show that the radiation pressure exerted by a beam of ultrasound can be used for contrast enhancement in high-resolution x-ray imaging of tissue and soft materials. Interfacial features of objects are highlighted as a result of both the displacement introduced by the ultrasound and the inherent sensitivity of x-ray phase contrast imaging to density variations. The potential of the method is demonstrated by imaging microscopic tumor phantoms embedded into tissue with a thickness typically presented in mammog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…2͑b͒ shows an enhancement of the phase contrast at the interfaces between the veins and the surrounding tissue in the liver, and a virtually complete suppression of the absorption contrast seen in the conventional phase contrast image, as expected from previous images taken with inanimate bodies. 7 Experiments were carried out with a morphologically accurate breast phantom ͑CIRS, Tissue Simulation & Phantom Technology Inc., Model M51͒ designed to mimic cysts and tumors for ultrasound, magnetic resonance, and x-ray testing. The phantom is designed and manufactured to reproduce accurately physical properties such as density and elasticity of breast tissue, breast cysts, and breast tumors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2͑b͒ shows an enhancement of the phase contrast at the interfaces between the veins and the surrounding tissue in the liver, and a virtually complete suppression of the absorption contrast seen in the conventional phase contrast image, as expected from previous images taken with inanimate bodies. 7 Experiments were carried out with a morphologically accurate breast phantom ͑CIRS, Tissue Simulation & Phantom Technology Inc., Model M51͒ designed to mimic cysts and tumors for ultrasound, magnetic resonance, and x-ray testing. The phantom is designed and manufactured to reproduce accurately physical properties such as density and elasticity of breast tissue, breast cysts, and breast tumors.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 When ultrasound propagates through an inhomogeneous medium, differential radiation pressure is exerted within the body depending on the local density and sound speed. 9 Application of such radiation pressure results in unequal displacements of objects within the body, 10 which are of sufficient magnitude to be recorded in a high resolution x-ray image.…”
Section: Introductionmentioning
confidence: 99%
“…By subtraction of the two images, motion-induced phase-contrast is obtained. The potential of this method was demonstrated by imaging microscopic tumour phantoms embedded into tissue with a thickness typically presented in mammography [129]. It is anticipated that this method may be used for the detection of small-size tumours and other lesions distinguished from surrounding tissues by their elastic properties and density differences as small as a few percent [129].…”
Section: Haptic Interface For Target Volume Definitionmentioning
confidence: 99%
“…Interestingly it has been reported that acoustic radiation pressure may also be utilized as a kind of ''phase-contrast agent'', which is based on the fact that local change in tissue density may result in change in its refractive index [129,130].…”
Section: Haptic Interface For Target Volume Definitionmentioning
confidence: 99%
“…If absorption contrast is not of primary interest since the method relies on the deflection of x-radiation rather than their absorption, it is possible to employ hard, weakly absorbed x-radiation providing a significantly lower absorbed radiation dose than that in conventional x-ray shadowgraphy. In order to produce phase contrast in an image, the x-ray source must have a high degree of spatial coherence; hence, x-ray synchrotrons [3][4][5] or microfocus x-ray tubes [6][7][8] are typically used as radiation sources. A further feature of employment of sources with high spatial coherence, in addition to the benefit of phase contrast in the image, is that if the image recording device is chosen to have high resolution, the obvious advantage of high spatial resolution also becomes characteristic of the method adding to its overall utility as an imaging diagnostic.…”
Section: Introductionmentioning
confidence: 99%